TINJAUAN RAGAM BENTUK TLUTUR DAN KORELASINYA - Suraji Suraji (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2013)
The background to this paper was the information that many Javanese musical compositions or gending in Surakarta style are formed from ‘sekar’ or tembang (a vocal melody or form of sung poetry). The main focus of this paper is the connections between Sendhon Tlutur, Ketawang Gendhing Tlutur, Ayakayakan Tlutur, Srepeg Tlutur, Sampak Tlutur, Ketawang Dhandhanggula Tlutur, and Sekar Macapat Dhandhanggula Tlutur, which were observed by comparing the vocal melody of Sendhon Tlutur with the musical phrases of the skeleton melody, or balungan, in Ayak-ayakan, Ketawang Gendhing, Srepeg, and Sampak, and the vocal melody of Ketawang Dhandhanggula with Sekar Macapat Dhandhanggula Tlutur. The theoretical basis that was used for analyzing the gending in question is Mantle Hood’s ‘evolution’ theory which states that culture (including the arts) is not static in nature but rather develops according to its needs. In addition to this evolution theory, the gending were analyzed using Mas Ngabehi Warsapradangga’s premise which states that the original source or foundation for composing a gending is a vocal melody or tembang. The results of the analysis of this study show that there are similarities between the melodic line of Sendhon Tlutur and Ayak-ayakan, Srepeg, Sampak, and Ketawang Gendhing Tlutur, while Ketawang Dhandhanggula Tlutur is a development of Sekar Macapat Dhandhanggula Tlutur.Keywords: various forms and correlation of gendhing tlutur